New heroes in antiquity: from Achilles to Antinoos - Jones, Christopher P. (Revealing antiquity, 2010)
Introduction -- Poetic heroes -- Local heroes -- Warriors and patriots -- Athletes, poets, philosophers -- Private heroes -- Greek heroes in a Roman world -- Antinoos -- Heroes and saints -- Appendix: Living heroes